STUDI ALUMNI STUDI ALUMNI TORAJA STT. INJIL BHAKTI CARAKA UNTUK MENGUKUR KEBERHASILAN PENDIDIKAN TEOLOGI MENGATASI KEPERCAYAAN MA' NENE' - Hartati Muljani Notoprodjo; Sara Sapan; Hiskia Lebang; Welly Welliam Polly (Jurnal Penjaminan Mutu, 2022)
Theological College aims to shape its students into leaders of the Lord's people who know the Lord and His ways and are capable to direct the people in accordance with His word (the Bible). The attainment of this goal needs to be ensured so that the education carried out is not in vain. This can be done through alumni study. One of the influential things in the lives of the students is the beliefs of the tribe from which they come from. Toraja tribe has ma' nene' tradition that is still strongly practiced. The purpose of this study is to determine changes of the Torajan alumni of STT. Injil Bhakti Caraka (STT. IBC) in their understanding of, belief about, and attitude toward the ma' nene' tradition after receiving their four-year theological education. The research was conducted using a qualitative method, through interviews of Torajan alumni in their understanding, beliefs, and attitudes towards ma' nene' before, during, and after studying at STT. IBC. This research found that 1) the alumni's understanding of ma' nene' has become comprehensive and profound, 2) their belief is in accordance with God's word, namely the spirit of the dead returns to God and has no power to give blessings or curses, and 3) their attitude is neither practicing nor promoting ma' nene', however not forbidding if a church member wants to do it, while at the same time educating him truth from God's words. These results show the success of the theological education carried out by STT. IBC.